Analisis Dampak Kenaikan Upah Minimum Provinsi, Terhadap Tingkat Pengangguran dan Tingkat Partisipasi Angkatan Kerja di Jakarta 2004 -2013 - Izzah, Niddaul (Transparansi : Jurnal Ilmiah Ilmu Administrasi, 2015)
This study analyzesthe impact of minimum wage increases to the provincial labor force participation rate in Jakarta. The results showed the increase in provincial minimum wage can reduce   unemployment   and   raiselabor   force   participation   rate   in   Jakarta.   To   lower   the unemployment rate in Jakarta, the provincial minimum wage should always be adjusted to the size of a decent standard of living. The unemployment rate would have a wide impacton the social, economic, and security in Jakarta.